2015
DOI: 10.1111/bju.13331
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of renal mass aggressiveness using clinical and radiographic features: a global, multicentre prospective study

Abstract: ObjectiveTo examine the ability of preoperative clinical characteristics to predict histological features of renal masses (RMs). Patients and MethodsData from consecutive patients with clinical stage I RMs treated surgically between 2010 and 2011 in the Clinical Research Office of Endourology Society (CROES) Renal Mass Registry were collected. Based on surgical histology, tumours were categorised as benign, low-or high-aggressiveness cancer. Multivariate logistic regression was used to estimate the probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…There is an increasing likelihood of malignancy and higher grade with increasing lesion size [ 34 , 44 , 45 ]. Of benign SRM that are surgically excised, 10–38% are found to be angiomyolipomas and 34–58% are found to be oncocytomas [ 46 48 ]. Ultrasound, contrast-enhanced CT and MRI may aid diagnosis (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing likelihood of malignancy and higher grade with increasing lesion size [ 34 , 44 , 45 ]. Of benign SRM that are surgically excised, 10–38% are found to be angiomyolipomas and 34–58% are found to be oncocytomas [ 46 48 ]. Ultrasound, contrast-enhanced CT and MRI may aid diagnosis (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For patients with small renal masses, age, sex, tumor size/location, symptoms, and smoking history are associated with risk of malignancy and aggressive malignancy. However, the discriminative accuracy of these clinical and imaging characteristics is poor to moderate 17,55–57 . It is possible that the addition of mpMRI to existing clinical prediction models improves accuracy and allows more patients to avoid tumor biopsy and/or treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the discriminative accuracy of these clinical and imaging characteristics is poor to moderate. 17,[55][56][57] It is possible that the addition of mpMRI to existing clinical prediction models improves accuracy and allows more patients to avoid tumor biopsy and/or treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, Logistic analyses demonstrated that ERTs with higher R score (OR, 3.32; 95% CI, 1.17-9.41; P=0.024) and N score (OR, 2.87; 95% CI, 1.66-4.96; P=0.021) were independently associated with MH and higher R score (OR, 3.74; 95% CI, 1.71-8.17; P=0.001) was independently associated with UP. Several studies have demonstrated that tumor size was significantly correlated with malignant and adverse pathological features ( 4 , 21 , 42 , 43 , 45 , 46 ). A retrospective study that included 592 patients with renal tumors by Violette, P. et al.…”
Section: Discussionmentioning
confidence: 99%